The Effect of BMN Assessment and Control in Supporting The Optimization of BMN Management and Its Implications for The Quality of Financial Statements at RSPR - Wintarsih, Winwin (Maksi, 2024)
This study was conducted to determine the effect of assessment and control of State Property (BMN) in supporting the optimization of State Property management and implications for the quality of financial statements case study at Lung Hospital dr. H.A Rotinsulu Bandung. This study was conducted using primary data obtained by distributing questionnaires. The population in this study was employees appointed as financial accounting officers, BMN accounting officers, heads of Accounting Teams and BMN, Head of Financial Implementation Team, Head of General and Household Team, and employees related to BMN in the dr. H.A Rotinsulu Bandung Lung Hospital which amounted to 50 respondents, the entire population in this study was sampled. Data analysis using the Statistical Package for The Social Sciences (SPSS) approach. The data analysis technique used is path analysis. The data analysis technique used is path analysis. The results of this study show that the assessment, control and supervision of State Property (BMN) in supporting the optimization of the management of State Property partially has a significant positive effect on the quality of financial statements.